2011
DOI: 10.1177/030089161109700608
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Radiotherapy with Intensity-Modulated Radiation Therapy for Advanced Hepatocellular Carcinoma

Abstract: Radiotherapy with intensity-modulated radiotherapy achieved a good response rate in patients with advanced hepatocellular carcinoma, and patients who had a good response lived longer than patients who did not have a good response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Zhou et al27 found T stage, PVT, radiation dose, and Child-Pugh classification to be significantly associated with overall survival in univariate analysis, and in Cox regression analysis, T stage, radiation dose, and Child-Pugh classification were independent prognostic factor for overall survival. Kang et al21 found significant associations of PVT, Child-Pugh classification, and primary tumor response with overall survival in univariate analysis, and in multivariate analysis, only primary tumor response remained significant. Kim et al19 reported the Cancer of the Liver Italian Program score and primary tumor response were significant prognostic factors for overall survival in univariate analysis, and only primary tumor response in multivariate analysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Zhou et al27 found T stage, PVT, radiation dose, and Child-Pugh classification to be significantly associated with overall survival in univariate analysis, and in Cox regression analysis, T stage, radiation dose, and Child-Pugh classification were independent prognostic factor for overall survival. Kang et al21 found significant associations of PVT, Child-Pugh classification, and primary tumor response with overall survival in univariate analysis, and in multivariate analysis, only primary tumor response remained significant. Kim et al19 reported the Cancer of the Liver Italian Program score and primary tumor response were significant prognostic factors for overall survival in univariate analysis, and only primary tumor response in multivariate analysis.…”
Section: Discussionmentioning
confidence: 96%
“…With the advent of IMRT technique, a few studies also reported the primary tumor response rates after IMRT in unresectable HCC. From a study of 27 HCC patients treated with IMRT, Kang et al21 reported an objective response rate of 44.4%. McIntosh et al22 treated 20 HCC patients with helical tomotherapy and concurrent capecitabine, and reported an objective response rate of 56.25%.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a considerable probability for the reactivation of HBV in HCC patients that receive chemotherapeutic drugs, which may be a fatal complication and may lead to disruption in treatment schedules (4). With the development of novel radiotherapy as 3-dimensional conformal therapy or stereotactic radiation therapy, the role of radiotherapy has become of increasing importance in the treatment of HCC, particularly for HCC patients with portal vein tumor thrombus (PVTT) or a tumor diameter <10 cm (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, IMRT has been used to treat moving tumors, such as, those of lung cancer or HCC [9-12]. McIntosh et al [10] prescribed 50 Gy in 20 fractions to 20 HCC patients using helical tomotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al [11] irradiated 40-50 Gy in 10 fractions to intra- and extra-hepatic lesions simultaneously using helical tomotherapy and found that 45% of intrahepatic lesions achieved more than partial response. Kang et al [12] prescribed 50.4 Gy in 28 fractions to 27 HCC patients by linear accelerator based IMRT, and 44% achieved better than partial response.…”
Section: Introductionmentioning
confidence: 99%